Recruitment of Live Donors by Candidates for Kidney Transplantation - Reese, Peter P. (American Society of Nephrology, 2008)
Background: Little is known about efforts that renal transplant candidates make to recruit live donors. It was hypothesized that preference for live donor kidney transplantation and greater knowledge about live donor transplantation are associated with candidates’ initiating conversations about donation with potential donors. Design, setting, participants, & measurements: A cross-sectional study of renal transplant candidates was performed at initial transplant evaluation. Candidates completed a questionnaire that specified whether they had initiated conversations about donation with any potential donors. The questionnaire also measured preference for live donor transplantation, knowledge about transplantation, concern about donor harm, willingness to ask for help in coping with kidney disease, and social support. Results: Ninety-six candidates participated. Forty-nine (51%) reported initiating a conversation with at least one potential donor. In multivariable logistic regression, domains associated with initiating a conversation included: preference for live donor transplantation, willingness to ask for help, and female gender. Older age was associated with a lower odds of initiating a conversation. Knowledge, concern about donor harm, social support, and ethnicity were not associated with initiating a conversation with a donor. Conclusions: Attempts at donor recruitment by kidney transplant candidates are common. These findings suggest that interventions that influence preferences about transplantation and willingness to ask others for help are logical targets to enhance access to live donor transplantation.